Cryptococcosis in patients with diabetes mellitus II in mainland China: 1993‐2015. Issue 11 (30th August 2017) - Li, Yingfang; Fang, Wenjie; Jiang, Weiwei; Hagen, Ferry; Liu, Jia; Zhang, Lei; Hong, Nan; Zhu, Yu; Xu, Xiaoguang; Lei, Xia; Deng, Danqi; Xu, Jianping; et al.
Summary: Diabetes mellitus II (DM II) is a newly defined independent factor contributing to the morbidity and mortality of cryptococcosis. This retrospective case analysis aims to explore the epidemiology, clinical profile and strain characteristics of cryptococcosis in Chinese DM II patients. This study included 30 cases of cryptococcosis with DM II occurring from 1993 to 2015 in mainland China. The hospital‐based prevalence of cryptococcosis in DM II was 0.21%. The mean age of the patients was 56.1 years (95% confidence interval: 51.5, 60.6), and 93% of the patients were older than 40 years. Sixty‐two per cent of the patients experienced untreated or poorly controlled blood glucose before infection. Multilocus sequence typing analysis categorised all cultured strains as Cryptococcus neoformans and sequence type 5. Sixty‐nine per cent of pulmonary cryptococcosis patients experienced misdiagnoses and treatment delays. Sixty per cent of cryptococcal meningitis patients received substandard antifungal therapy. The overall death rate was 33%. Considering the large population size of DM II patients in China, improved attention should be paid to the high prevalence of cryptococcosis as revealed by us. We also emphasised the importance of blood glucose control for infection prevention, especially among the elderly.